Three-dimensional computational analysis of performance improvement in a novel designed solar photovoltaic/thermal system by using hybrid nanofluids - Öztop, Hakan Fehmi; Sahin, A. Z.; Cosanay, Hakan; Sahin, I. H. (Pergamon-Elsevier Science Ltd, 2023)
In the present study, the effect of using hybrid nanofluids on the performance of the novel solar photovoltaic/ thermal (PV/T) system is analyzed for possible maximization of the overall efficiency that includes both electrical and thermal energy yields. A novel design has been performed to transfer heat from the backside of a solar collector to water. Three-dimensional (3D) Computational fluid dynamics (CFD) method was applied by using finite volume method (FVM). The governing parameters are Reynolds number (100 <= Re <= 1500), heat flux (400 <= q <= 800) and different types of nanofluids such as single or hybrid nanofluids at different combinations. A considerable improvement is observed in the performance of the PV/T system when using hybrid nanofluids instead of pure base heat transfer fluids or single type nanofluids.
Keywords: Photovoltaic thermal; Hybrid nanofluid; Heat transfer enhancement; Energy; Solar energy; Computational fluid dynamics